Conhecimentos profissionais e referenciais de conhecimentos - Bernard Prot (Universidade do Porto, 2009)
Using empirical materials from studies about professional training and the validation of acquired experience this text is interested in work that is to "raise" the qualification level of experienced workers, as suggested in the European Directives. The adopted point of view is the analysis of the activity, precisely the activities that relate the knowledge developed at work with the abstract knowledge contained in the referential systems of training courses or diploma. Following Vygotsky´s theory, revisited by contemporary works, we study the conditions that allow the beginning of a potential double development: leading the renewal of the action as well as abstract concepts.